Effects of Energy Level on Oestrous Behaviour and Follicular Development in Cattle in Malaysia - Amri, Azizah (2008)
The understanding of the development and growth of an ovulatory follicle within the ovary is important in order to improve the efficiency of breeding techniques such as artificial insemination (Al) and embryo transfer. The objectives of the study were to determine the effects of different levels of energy diets on characteristics of oestrous behaviour by visual observation, and follicular development in cows. The experiments were conducted to determine the oestrous behaviour by visual observation and the effects of dietary energy levels on follicular development in crossbred cows offered different levels and duration of energy diets. Thirty crossbred Kedah-Kelantan (KK) cows were divided into two groups, I) n=15; received grass with maintenance supplement and II) n=15; received grass with double maintenance supplement. Oestrous was initially synchronised using chloprostenol intra vaginal progesterone releasing device (CIDR-B@) containing 1.38 g progesterone for 7 days and administered 1 ml synthetic prostaglandin analogue 2 days before CIDR-B@ removal. The cows were observed for estrous behaviour continuously 24 hours daily for 72 hours immediately after CIDR-B@ removal. The ovaries then were visualized using 7.5 MHz linear array transrectal transducer attached to a real-time, B mode portable ultrasound. Scanning was carried out from six hours at the beginning of estrous and repeated every six hours until ovulation. The day of first detection of a 2 4 rnm follicle identified as a dominant follicle was taken as the first day of a follicular wave. During each ultrasound examination, a single blood sample was drawn and collected into 10 ml plain tubes for determination of progesterone concentration. A timed insemination was performed at 48 to 54 hrs after removal of CIDR-BB for all cows. Pregnancy diagnosis was performed using ultrasonography and rectal palpation techniques. In expressing oestrous behaviour characteristics, there were no differences between group of single maintenance (GSM) and group of double maintenance (GDM) (p>0.05) in the first cycle, while in the second cycle, characteristics of oestrous behaviour were clearly seen. The results obtained showed that approximately 33.3% of GSM and 40% GDM cows produced 2 waves of follicular development while 66.67% of GSM and 60% of GDM cows produce 3 waves of follicular development. Both GSM and GDM had equal number of cows producing 2 and 3 waves of follicular development. However, the number of waves of folliwlar development, length of estrous cycle, growth and regression rate of dominant follicle, and progesterone concentration between GSM and GDM were not significantly different (p>0.05). Therefore, the results from the experiment suggest that the higher and longer period of energy levels would not accelerate the estrous behaviour and increased the number of animals pregnant. From the study, it was concluded that cows offered double maintenance levels of energy diet was not significantly different from cows offered single maintenance levels of energy diet in terms of exhibit oestrous behaviour, follicular development and number of animal pregnant (P>0.05).